An Analysis of Flouting of Maxims of Quality in the “Uptown Girls” Movie Used by the Main Character - Marianus Indra Wayon; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
The study, entitled "Flouting Maxim of Quality in the Film Uptown Girls (2003)," aims to identify and analyze the types of flouting of the maxim of quality and the reasons why the main character, Molly Gunn, flouts this maxim throughout the film. The data for this research were collected from the film Uptown Girls (2003), focusing on utterances by Molly Gunn that contain instances of sarcasm, hyperbole, deliberate lies, and unsupported statements. This study applied observation and transcription methods, analyzed using a descriptive qualitative approach. The analysis was supported by Grice’s (1975) theory of the Cooperative Principle, specifically the maxim of quality, to categorize the types of flouting. Furthermore, the reasons behind Molly’s flouting were interpreted based on pragmatic functions such as emotional expression, self-defense, and social interaction. This study collected 50 instances of flouting the maxim of quality, including 14 cases of deliberate lies, 13 hyperboles, 12 sarcasms, and 11 unsupported statements. The analysis reveals that Molly Gunn’s floutings are not accidental but serve as deliberate communicative strategies to reflect her emotional vulnerability, identity assertion, and relational dynamics. Based on the results, it can be concluded that deliberate lie is the most frequently used flouting type, and the pragmatic motivation behind these utterances is primarily to preserve self-image and engage the audience through implied meaning.